IMF and the Environment - Gandhi, Ved (Pamphlet Series; Pamphlet Series, No., 1998)
In recent years, observers have called on the IMF to pay closer attention to certain issues that do not fall directly within its mandate, such as the environment. This booklet reviews IMF's approach to environmental issues and when and how the IMF integrates environmental concerns into its work.